The cultural construction of cellular agriculture food: through the lens of the whole-parts framework for meat - Hibino, Aiko; Minari, Jusaku; Takahashi, Kento; Sugiyama, Yuko; Kawana, Shinji (Frontiers in Sustainable Food Systems, 2024)
This essay presents a critical perspective on the nature of what is referred to as “cultured meat” in the public sphere by revisiting the concept of meat in cultural practice. We propose a perspective that focuses on and further investigates whether cultured meat is meat, examining the interaction between the emergence of cellular agriculture technologies and cultural practices. First, we review the production processes of cellular agriculture for meat, comparing this to the processes used to produce conventional meat. Second, we discuss how meat has been embedded in cultural practices, focusing on meat-related activities, and propose that a whole-parts relationship is critical for constructing the meaning of meat in cultural contexts. Third, several key issues raised in the social debate on cultured meat are addressed within the whole-parts framework. Cultured meat requires a complete bottom-up process in producing objects, indicating that the concept of cultured meat is not necessarily aligned with the concept of existing meat, as previously suggested from the perspective of producing conventional meat. In this perspective, we proceed to further investigation the meaning of meat in cultural constructions, wherein the relationship between the whole body and meat as a part of it is important. Thus, cultured meat can be considered a nonmeat under the whole-parts framework for meat. This insight can provisionally and speculatively update some of the ethical, legal, and social issues of cultured meat as well as products based on cellular agriculture technologies.